Governing Health in Contemporary China. - Huang, Yanzhong (China policy series., 2012)
The lack of significant improvement in people's health status and other mounting health challenges in China raise a puzzling question about the country's internal transition: why did the reform-induced dynamics produce an economic miracle, but fail to reproduce the success Mao had achieved in the health sector? This book examines the political and policy dynamics of health governance in post-Mao China. It explores the political-institutional roots of the public health and health care challenges and the evolution of the leaders' policy response in contemporary China. It argues that reform-in.